2018
DOI: 10.1353/hpu.2018.0028
|View full text |Cite
|
Sign up to set email alerts
|

Higher Perceived Clinic Capacity to Address Patients' Social Needs Associated with Lower Burnout in Primary Care Providers

Abstract: Provider perceptions of greater clinic capacity to address SN are significantly associated with lower burnout. Devoting organizational resources to address SN may reduce PCP burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 1 publication
1
54
0
Order By: Relevance
“…Several recent studies have found that provider burnout is lower when providers perceive their healthcare organizations to have the capacity to address patients' social needs. 30,31 With provider burnout estimated to cost from $2.6 to $6.3 billion per year, reducing turnover could provide substantial economic benefits. 32 At the same time, requiring providers to screen and provide social needs referrals on a routine basis could also increase provider burnout by adding yet one more requirement to already full schedules.…”
Section: Reduced Provider Burnoutmentioning
confidence: 99%
“…Several recent studies have found that provider burnout is lower when providers perceive their healthcare organizations to have the capacity to address patients' social needs. 30,31 With provider burnout estimated to cost from $2.6 to $6.3 billion per year, reducing turnover could provide substantial economic benefits. 32 At the same time, requiring providers to screen and provide social needs referrals on a routine basis could also increase provider burnout by adding yet one more requirement to already full schedules.…”
Section: Reduced Provider Burnoutmentioning
confidence: 99%
“…Further work is therefore required to understand how best to support patients and professionals in this area, for it was also clear that our participants not only valued the possibility of more empathy and understanding from their health care professionals but could also imagine that this would get them access to practical support and appropriate advice. Interestingly, none talked about looking for support in gaining more access to nancial resources -the root cause of their food insecurity -and is something that we suspect could be a barrier on the part of health care professionals to raising the issue, who may feel powerless to do much about it [93]. This particular nding (the invisibility of nancial vulnerability within the health care consultation) challenges orthodox notions of selfmanagement support policy and practice within health care settings (in UK and internationally).…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings also help to explain other recent work linking burnout and capacity to address social needs. 22,[24][25][26] Having dedicated team members directly address social needs helped clinicians stay engaged and feel more connected with their patients, which is a major source of work-related satisfaction for clinicians. 39,40 The findings also highlight how structural challenges-including lack of reimbursement, inadequate integration between medical and social delivery systems, and insufficient nonclinical capacity to address social needs-presented key barriers to professional efficacy, an important component of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated direct or potential links between clinician burnout and the ability to address patients' social needs. [22][23][24][25][26] One study showed that primary care clinicians reporting extreme stress were more likely to rate patients' social or financial issues as most relevant to patient complexity. 22 Lower satisfaction with resources for treating complex patients has been associated with more symptoms of burnout 23 ; conversely, practice preparedness to address social needs and ease of coordinating social services have been associated with greater clinician satisfaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation